Analysis of Economic Disparities and Leading Sectors Between Lombok and Sumbawa Islands, 2020–2024 - Utami, Mimi Sri; Emi Salma (Manunggal Halim Jaya, 2026)
Regional economic disparities between Lombok Island and Sumbawa Island remain a major development challenge in West Nusa Tenggara Province (NTB), particularly in terms of uneven sectoral growth and regional economic concentration. This study analyzes the economic structure and identifies leading sectors in NTB during the 2020–2024 period using the Klassen Typology and Location Quotient (LQ) methods. The analysis employs secondary data on Gross Regional Domestic Product (GRDP) at constant 2010 prices published by the Central Statistics Agency, supported by relevant literature. Economic sectors are classified based on their growth rates and contributions to GRDP to distinguish advanced and fast-growing sectors, potential sectors, and relatively underdeveloped sectors. The findings indicate that regions on Lombok Island—especially Mataram City and West Lombok Regency—are dominated by advanced and fast-growing sectors, primarily modern services such as trade, transportation, accommodation and food services, finance, education, and health. In contrast, Sumbawa Island is characterized by a concentration in agriculture, fisheries, mining, and basic services, which largely fall into the potential or relatively underdeveloped categories. LQ analysis further confirms that Lombok Island’s economic base is driven by trade, tourism, real estate, and educational services, while Sumbawa Island relies more heavily on agriculture, construction, and mining sectors. These findings demonstrate persistent regional economic disparities in NTB and highlight the need for region-specific development policies. The future development strategy is directed at strengthening the base sector in each region, diversifying the economy, and strengthening connectivity between regions to create inclusive and equitable growth.